The influence of some factors on Litter Size in Cyprus, local goats and their crosses: أحمد عبدالرضا مناتي , و سعد ابراهيم سعيد , و صادق علي طه - مناتي أحمد عبد الرضا; ابراهيم سعيد سعد; علي طه صادق (Journal of Kerbala for Agricultural Sciences, 2017)
Data were analyzed from 461 record for goats from ruminant research station of the Ministry of Agriculture and obtained from 314 CY record 107 Local record and 40 cross record , study aimed to determine the impact of some factors on the litter size of three genetic groups of goats The results showed that average General status of the number of litter size is 2.04 birth/kidding of this study, and found high significant effect 0.01 ≥P genetic group in the litter size where marked Cyprus an average of 2.24 ± 0.07 birth/ kidding while the lowest performance was the cross goats an average of 1.91 ± 0.13 birth/ kidding , there was a high significant effect 0.01 ≥P for the month - year of birth where best period was April -2012 and March and April -2013 on the other periods, as well as there was a high significant effect 0.01 ≥P to the age of the goat at birth in the litter size where mothers age of one year and the age of five years on the rest of the year and an average of 2.46 ± 0.28 and 2.27 ± 0.11 birth/kidding respectively .